(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Arka Kalpana is a distinctive Ayuvedic pharmaceutical preparation in which the active principles and volatile components of a drug are extracted with the help of Arka yanthra or another practical modern distillation apparatus. Tamboola Arka is a preparation mentioned in third Shataka of Arka Prakasha. It has properties to cure the Mukha dourgandhya, Mala, Vata and Srama nashana. Tamboola pathra has Katu, Tikta, Kashaya rasa and Laghu, Tikshna Vishada gunas by which it can be used to control the diseases which occur inside the mouth. Since it is an Arka preparation it has got several benefits like shelf life and is also user friendly. No previous works have been carried out on Tamboola Arka. So in this study Tamboola Arka was prepared and organoleptic and physico-chemical parameters were tested. GCMS (Gas Chromatography and Mass Spectrometry) was also conducted to identify the various components and their concentrations.